2002
DOI: 10.1104/pp.011049
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of the Gene for Soybean Hydroxyisourate Hydrolase. Localization and Implications for Function and Mechanism

Abstract: The gene encoding hydroxyisourate hydrolase, a novel ureide-metabolizing enzyme, has been cloned from soybean (Glycine max). The gene encodes a protein that is 560 amino acids in length and contains a 31-amino acid signal sequence at the N terminus that is not present in the mature protein. The presence of two SKL motifs near the C terminus suggests that the protein resides in the peroxisome. This expectation is borne out by results from immunogold electron microscopy, which revealed that hydroxyisourate hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…Tipton and colleagues have provided details of the urate oxidase-catalyzed reaction (5,6) and subsequently identified a gene for HIUHase from soybean (G. max) (7,8). The 560-aa soybean HIUHase does not share any sequence similarity with PucM, but belongs to family 1 of glycosidase (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tipton and colleagues have provided details of the urate oxidase-catalyzed reaction (5,6) and subsequently identified a gene for HIUHase from soybean (G. max) (7,8). The 560-aa soybean HIUHase does not share any sequence similarity with PucM, but belongs to family 1 of glycosidase (9).…”
Section: Discussionmentioning
confidence: 99%
“…1.7.3.3; uricase), but recent investigations have revealed that this pathway includes two additional, distinct, chemically labile intermediates: 5-hydroxyisourate (HIU) and 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline (OHCU) (5,6). It is now generally believed that urate oxidase is responsible only for the conversion of uric acid into HIU, and a second enzyme, HIU hydrolase (HIUHase), catalyzes the hydrolysis of HIU into OHCU (7)(8)(9)(10)(11), which is then converted into allantoin via an enzyme-dependent decarboxylation reaction (Scheme 1) (11). Recently, three genes were characterized as HIUHases: a soybean (Glycine max) gene (7,8), PucM in Bacillus subtilis (10), and MuraH in mice (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, GH1 has been most thoroughly documented and shown to comprise a gene family encoding 40 putative functional GHs in Arabidopsis (Arabidopsis thaliana) and 34 in rice (Oryza sativa) in addition to a few pseudogenes (Xu et al, 2004;Opassiri et al, 2006). In addition to b-glucosidases, plant GH1 members include b-mannosidases (Mo and Bewley, 2002), b-thioglucosidases (Burmeister et al, 1997), and disaccharidases such as primeverosidase (Mizutani et al, 2002) as well as hydroxyisourate hydrolase, which hydrolyzes the internal bond in a purine ring rather than a glycosidic bond (Raychaudhuri and Tipton, 2002). The specificity for the glycone in GH1 enzymes varies.…”
mentioning
confidence: 99%
“…The first step in this pathway is the degradation of nucleic acid purine moieties (adenine and guanine) to uric acid. After two consecutive oxidation reactions by urate oxidase and hydroxyisourate hydrolase, the uric acid is converted to ALN (Raychaudhuri and Tipton, 2002). Allantoinase (ALN amidohydrolase, EC 3.5.2.5) catalyzes the hydrolysis of ALN to form allantoic acid, which is a key reaction for biogenesis and the degradation of ureides (Vogels et al, 1966;Noguchi et al, 1986).…”
mentioning
confidence: 99%